Ensuring SDG-sensitive development cooperation - Alexandra Rudolph (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
The 2030 Agenda for Sustainable Development challenges domestic and international actors. The Sustainable Development Goals (SDGs) represent a multidimensional approach to development and are consequently aimed at all countries. To ensure SDG-sensitive cooperation it is not only necessary to adapt the allocation of official development assistance (ODA) to the requirements of the agenda, but also to reinforce the role of development cooperation in international cooperation. However, there is a lack of clear guidelines for adaptation and reform. Using five strategic questions of donor decision making, the objective is to illustrate what SDG-sensitive development cooperation includes. The reform potential of the 2030 Agenda and the effectiveness of ODA giving are significantly dependent on the ability of donors to adjust their cooperation criteria, mechanisms and instruments towards the aims of the agenda. They should focus to a greater extent on the priorities of partners and the global common good, to co-ordinate themselves and focus on their comparative advantages. The goal is to establish development policy as an instrument to achieve policy coherence and reinforce the high development-relevant standards of the 2030 Agenda as underlying principles for international cooperation in all policy fields. The following recommendations for SDG-sensitive development cooperation can be derived from the 2030 Agenda: Allocation channel: Global public goods are central to the realisation of the 2030 Agenda. Therefore, the multilateral channel should be strengthened. Country selection: SDG-sensitive ODA allocation is based on the division of labour amongst donors and supports particularly under-developed countries in the realisation of the agenda. In cooperation with emerging countries it strengthens their international responsibility and the reduction of inequalities between and within countries. Sector selection: SDG-sensitive sector selection requires strategic coordination and the reliable division of labour amongst donors. This enables donors' profile formation and broad national support for the agenda. However, country-specific cooperation with each partner is also central. Instruments: An SDG-sensitive instrument-mix is adapted to the conditions of the partner country and makes increased use of local systems. Evidence-based and flexible instruments contribute significantly to this. ODA as catalyst: ODA can only be catalytic if the 2030 Agenda is realised, with the creation of development-relevant standards and regulations that enable the mobilisation of national, public and private investment. These recommendations require further systematic analysis to enable learning processes and design development cooperation adaptively. The objective should be an evidence-based policy that reacts to changing conditions and is transparent and aware of its responsibility.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Entwicklungsfinanzierung und öffentliche Finanzen